Influenza Vaccination for the Prevention of Cardiovascular Disease in the Americas: Consensus document of the Inter-American Society of Cardiology and the Word Heart Federation. Issue 1 (5th August 2021) - Liprandi, Álvaro Sosa; Liprandi, María Inés Sosa; Zaidel, Ezequiel José; Aisenberg, Gabriel M.; Baranchuk, Adrián; Barbosa, Eduardo Costa Duarte; Sánchez, Gabriela Borrayo; Alexander, Bryce; Zanetti, Fernando Tomás Lanas; Santi, Ricardo López; Múnera-Echeverri, Ana Girleza; Perel, Pablo; et al.
Background: Cardiovascular mortality is decreasing but remains the leading cause of death world-wide. Respiratory infections such as influenza significantly contribute to morbidity and mortality in patients with cardiovascular disease. Despite of proven benefits, influenza vaccination is not fully implemented, especially in Latin America. Objective: The aim was to develop a regional consensus with recommendations regarding influenza vaccination and cardiovascular disease. Methods: A multidisciplinary team composed by experts in the management and prevention of cardiovascular disease from the Americas, convened by the Inter-American Society of Cardiology (IASC) and the World Heart Federation (WHF), participated in the process and the formulation of statements. The modified RAND/UCLA methodology was used. This document was supported by a grant from the WHF. Results: An extensive literature search was divided into seven questions, and a total of 23 conclusions and 29 recommendations were achieved. There was no disagreement among experts in the conclusions or recommendations. Conclusions: There is a strong correlation between influenza and cardiovascular events. Influenza vaccination is not only safe and a proven strategy to reduce cardiovascular events, but it is also cost saving. We found several barriers for its global implementation and potential strategies to overcome them.